Developing Question Items Through Quizizz in Grade X MAN 1 Blitar - Endang Lestari Rahayu; Istina Atul Makrifah; Widiarini Widiarini; Tyas Alhim Mubarok (Journal of Development Research, 2022)
This study aims to develop question items through quizizz application for students of class X Religious 1. Based on the results of interviews with 21 students. Learning english in the classroom during the pandemic many students have difficulty in reading skills because students cannot practice it directly with their teacher and friends. In addition to being a student, which makes students bored with monotonous lesson. This research and development refers to the Borg and Gall design. The data collection instrument used was a questionnaire. The data collection techniques were interviews and observations.The Process of developing question items through quizizz application is research and development steps are: (1) Potential and problem, (2) Data collection, (3) Product design, (4) Design validation, (5) Design revision, (6) Product testing, (7) Trial use, and (8) Product revision. The results of developing question items through quizizz application is the researcher analyzed the data from a questionnaires by presenting it and then comparing it with the validity criteria, the data obtained was 70.3% from media expert and 63% from material expert, which means valid or feasible to use. From the teacher have 79% is valid and feasible to be more active in learning. After being tested for effective and practical development products, this is evidenced by the analysis of students satisfaction questionnaires which is used as the main reference for product feasibility. The data results show 76.6% which means students are very helped and motivated by the help of learning media application from the product.